IDENTIFIKASI GOLONGAN SENYAWA TOKSIK DARI EKSTRAK METANOLIK DAUN Piper spp.TERHADAP SEL KANKER PAYUDARA T47D - , Rohmat Priya Atmaja ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Several species of Piper spp. has know for cytotoxic activities. The activity come from compounds that belong to secondary metabolite. Cis-yagonin and flavokavain B compounds isolated from P. methysticum are having cytotoxic activities to leukemia and ovary cancer cell. The ethanolic extract of P. crocatum has cytotoxic activity to breast cancer T47D cell line. The metabolites content from ethanolic extract P. crocatum are alkaloids, saponin, tannin, and flavonoids. The purposes of the research to analyses cytotoxic activity of Piper spp. and the compound class which has cytotoxic property are identified. Soxhletation method with methanol as a solvent was selected for the extraction procedure. The leaves from 10 species of Piper spp. were collected from Bogor Botanical Garden. MTT assay was used for cytotoxic assay to cell line T47D. The component from the extract which had a highest cytotoxicity, was separated by vacuum liquid chromatography (VLC). The fractions from the VLC with highest cytotoxic activity was separated by preparative thin layer chromatography (PTLC). TLC was selected to monitor the constituent from the whole extract, fraction from VLC and PTLC. The compounds class from part of PTLC with highest cytotoxic activity are determinated by spray reagents. The highest cytotoxic activity came from P. porphyrophyllum extract (IC50= 667,5 Î¼g/ml). Cytotoxic activity from the constituent of the whole extract P. porphyrophyllum less active than the whole extract and doxorubicin (IC50 VLC fraction= 1.389,14 Î¼g/ml